Identification of Catur Gatra Tunggal Concept at Alun-Alun Malang Today’s - Wiwik Dwi Susanti; Dyan Agustin (Future Science)
Catur gatra tunggal is an important part of the alun-alun traditional concept on the Java island. When observed that the alun-alun traditional does not stand alone but is supported by the surrounding building. The function of the surrounding building are the palace, mosque, and market. The concept is the embodiment of the concept of catur gatra tunggal. The meaning of catur gatra tunggal is the four elements into one unity. Alun-alun here serves as the center as well as supporting all three activities in surrounding buildings. So the alun-alun itself is divided into three major zones of cosmos, culture and power. Today alun-alun Malang and surrounding buildings have many changes. Changes that occur in the form of physical and nonphysical aspects. So the existence of the concept of catur gatra tunggal as an important part of the alun-alun is still questionable. In this study attempted to identify the concept of a catur gatra tunggal on the alun-alun of the present. The process of identification is not only done by the method of observation but also the understanding of the concept of catur gatra tunggal as a whole. The hope of knowing the quality of catur gatra tunggal and the surrounding environment can provide an understanding that there is a shift in the concept of the alun-alun traditional into ordinary public space without meaning.